Application of a Genetic-Fuzzy FMEA to Rainfed Lowland Rice Production in Sarawak: Environmental, Health, and Safety Perspectives - Sang, Anisia J.; Tay, Kai Meng; Chee, P. Lim; Saeid, Nahavandi (IEEE, 2018)
Anisia J. Sang1 , Kai M. Tay1 , Chee P. Lim2 and Saeid Nahavandi2 ,